The Forced Sale of Real - Estate Property Aspects Regarding Procedure and Private International Law - Creț, Daniela Cristina; Berlingher, Daniel (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
Indirectly enforcement is regulated by the Code of Procedure, as a form of enforcement, seeks the recovery of the creditor’s claim through valorization of the debtor’s property or the seizure of income that it has to receive from a third party. Collection action on real estate as a form of indirect civil enforcement is made by the forced sale of immovable property belonging to the pursued debtor, so that the pursuing creditor would cover the claim. In this scientific approach we will examine the issues of pre-sale formalities, the sale and auctioning of real estate property and adjudicating the real-estate property in the regulation of the Code of Civil Procedure, which came into force in February 2013, as well as in the provisions of private international law incidental in the matter.